2014
DOI: 10.4238/2014.january.8.1
|View full text |Cite
|
Sign up to set email alerts
|

Gender flip-flop association between genetic variations of NEDD4L and metabolic syndrome in the Kazakh general population

Abstract: ABSTRACT. Genetic variation is thought to contribute to etiology of metabolic syndrome (MS). Neural precursor cell expressed developmentally downregulated 4-like gene (NEDD4L) is a candidate gene for MS. This study investigated the relationship between variations of NEDD4L and MS in the Kazakh, which is an ideal population to study the genetic mechanisms of complex diseases such as MS. We screened the promoter and exons of NEDD4L in 48 Kazakh individuals with MS to identify representative variations. By genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In addition, a SNP close to NEDD4L is strongly associated with the serum level of a liver enzyme, gamma-glutamyl transferase (p-value of 3 × 10 −12 ) in a GWAS 34 . In other genomic studies, NEDD4L has also been shown to be associated with hypertension 35 , obesity 36 , smoking and cancer 37 among a homogeneous population of Chinese Kazakh herders. Although these informative studies shed light on the associations of NEDD4L and hypertension and smoking independently, our study expands this work by examining and the independent and interactive effects of genetics and smoking on blood pressure among an African American population.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, a SNP close to NEDD4L is strongly associated with the serum level of a liver enzyme, gamma-glutamyl transferase (p-value of 3 × 10 −12 ) in a GWAS 34 . In other genomic studies, NEDD4L has also been shown to be associated with hypertension 35 , obesity 36 , smoking and cancer 37 among a homogeneous population of Chinese Kazakh herders. Although these informative studies shed light on the associations of NEDD4L and hypertension and smoking independently, our study expands this work by examining and the independent and interactive effects of genetics and smoking on blood pressure among an African American population.…”
Section: Discussionmentioning
confidence: 83%
“…However, an independent and much larger GWAS study of 3431 patients with breast cancer found significant association ( p = 4.1 × 10 −6 ) but with the opposite allele. This is highly relevant for transfer to the clinic, and we note here that there are many examples in the literature with a flip-flop effect in which the opposite alleles of the same variant are associated with increased risk of disease, which occur when the investigated variant is correlated with the true causative/functional variant through interactive effects or linkage disequilibrium which differs between populations [ 57 , 58 , 59 , 60 ]. Therefore, what may be required to truly move this gene towards clinical guidance is additional fine mapping and exon sequencing across different populations of patients with anthracycline-induced heart failure.…”
Section: Genetic Variants Associated With Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%